CEACAM6 promotes cisplatin resistance in lung adenocarcinoma and is regulated by microRNA‐146a and microRNA‐26a. Issue 9 (10th July 2020) - Du, He; Li, Yang; Sun, Rongrong; Yuan, Yuan; Sun, Sanyuan; Zhang, Youwei
Abstract : Background: Carcinoembryonic antigen (CEA)‐related cell adhesion molecule 6 (CEACAM6) is a glycophosphoinositol‐anchored glycoprotein which mediates cell‐cell interactions. Here, we aimed to explore the specific functions and regulatory mechanisms of CEACAM6 on cisplatin (DDP) in lung adenocarcinoma (LUAD). Methods: RNA sequencing was performed in the DDP‐resistant A549/DDP cell line and parental A549 cell line; miRNA expression profiling of the two cell lines was analyzed using GEO data (GSE43249). Gain‐ and loss‐of‐function experiments were used to investigate the biological function of CEACAM6 in vitro. The expression status and prognostic value of CEACAM6 in LUAD were verified using The Cancer Genome Atlas (TCGA) database. Results: CEACAM6 was first screened to be one of the most significantly upregulated genes in the DDP‐resistant A549/DDP cell line compared to the parental A549 cell line. Combined with computational prediction of candidate miRNAs that target CEACAM6, miR‐146a and miR‐26a were selected and verified by qPCR and luciferase reporter assay. The knockdown of CEACAM6 expression in A549/DDP cells inhibited cell proliferation, invasion and migration, decreased the IC50 values of DDP, and caused a significant downregulation of N‐cadherin, vimentin, Sox2, Oct4 and GTP‐RhoA and upregulation of E‐cadherin; while CEACAM6 overexpression in A549 cells resulted in the opposite effects. Of note, both miR‐146a and miR‐26a could counteract the biological effects of CEACAM6. Furthermore, CEACAM6 mRNA expression was significantly unregulated in DDP‐resistant LUAD tissues of TCGA database. Conclusions: CEACAM6 promotes DDP resistance in LUAD by affecting the epithelial‐mesenchymal transition (EMT) phenotype and stemness, which is post‐transcriptionally regulated by miR‐146a and miR‐26a. Abstract : CEACAM6 expression is upregulated in the DDP‐resistant LUAD cells and tissues. CEACAM6 promotes DDP‐resistance via regulating EMT, stemness and RhoA activation. miR‐146a and miR‐26a could counteract biological effects of CEACAM6.